Do Accounting Firm Consulting Revenues Affect Audit Quality? Evidence from the Pre‐ and Post‐SOX Eras - Lisic, Ling Lei; Myers, Linda A.; Pawlewicz, Robert; Seidel, Timothy A. (Contemporary Accounting Research, 2019)
ABSTRACT In recent years, public accounting firms have experienced a steady increase in the proportion of their revenues generated from consulting services. Although growth in consulting revenue following the Sarbanes‐Oxley Act (SOX) has been generated primarily from services provided to nonaudit clients, regulators have expressed concerns about the potential implications of this increase for audit quality. In contrast, accounting firms assert that the expertise developed by their consulting professionals helps them to provide better quality audits. We examine the relation between the proportion of accounting firm consulting revenue to total revenue and audit quality and investor perceptions of audit quality. Because SOX drastically altered the source of consulting revenues for public accounting firms, we also separately examine these relations in the pre‐ and post‐SOX eras. We find evidence suggesting that before SOX, higher proportions of audit firm consulting revenues negatively impacted both audit quality and investor perceptions of audit quality. However, we do not find a statistically significant association between audit firm consulting revenues and either audit quality or investor perceptions of audit quality following SOX. Our analyses suggest that even if these relations exist following SOX, the potential economic magnitude of the effect is small.